2014
DOI: 10.1517/13543784.2015.978283
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in early clinical development for the treatment of female sexual dysfunction

Abstract: Medications in early phase trials show promise for the treatment of FSD. These therapies focus on treating many possible causes of FSD. Concerns over gender bias within the FDA need to be resolved given the need for new treatment options for FSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Rather, in our opinion, the study adds to the extant literature indicating that female sexuality is not readily modifiable via agents. In this regard, whereas some studies have found improvements in sexual function following administration of saffron [55], tribulus terrestris [56], and flibanserin [57] for women suffering from hypoactive sexual desire disorder or SSRI-I SD, and whereas efforts are being made to identify new avenues to improve women's hyposexual function or SSRI-I SD [58], it remains unclear to what extent previous findings have found improvements but without achieving full remission to normal levels of sexual desire. In this context, given a tendency not to publish zero effects, it is also unclear whether the small number of publications reporting a favorable effect of agents on females' sexual function reflects this form of publication bias.…”
Section: Discussion ▼mentioning
confidence: 96%
“…Rather, in our opinion, the study adds to the extant literature indicating that female sexuality is not readily modifiable via agents. In this regard, whereas some studies have found improvements in sexual function following administration of saffron [55], tribulus terrestris [56], and flibanserin [57] for women suffering from hypoactive sexual desire disorder or SSRI-I SD, and whereas efforts are being made to identify new avenues to improve women's hyposexual function or SSRI-I SD [58], it remains unclear to what extent previous findings have found improvements but without achieving full remission to normal levels of sexual desire. In this context, given a tendency not to publish zero effects, it is also unclear whether the small number of publications reporting a favorable effect of agents on females' sexual function reflects this form of publication bias.…”
Section: Discussion ▼mentioning
confidence: 96%
“…The Female Sexual Distress Scale (FSDS) (17) scale comprises 12 questions that have been shown to provide a valid evaluation of sexually related personal distress in women in the past 30 days. Response choices are never (0), rarely (1), occasionally (2), frequently (3), and always (4). With each of the 12 items summed, the total score may range from 0 (no sexually related personal distress) to a maximum of 48 points (highly distressed).…”
Section: Questionnairesmentioning
confidence: 99%
“…Hypoactive sexual desire dysfunction is defined as persistently or recurrently deficient sexual fantasies and desire for sexual activity causing significant distress, all of which must be present for at least 6 months with a frequency of 75% to 100% (3). Pharmacologic treatment for female HSDD such as intranasal testosterone, sublingual testosterone with sildenafil, topical alprostadil, or intravaginal dehydroepiandrosterone are still under investigation in early phase clinical trials but have shown some promising effects (4). Oxytocin, a nanopeptide produced in the hypothalamus, acts both centrally and peripherally, where it is most commonly known for its actions during parturition and lactation.…”
mentioning
confidence: 99%
“…Burada uyarılma ve orgazmik cevapta anlamlı iyileşme ve ağrıda anlamlı azalma rapor edildi, cinsel istek azlığında ise etkinlik belirlenmedi. [20,21] Umut Bağlanmış Moleküller Doku selektif östrojen kompleksi (TSEC), vazoaktif intestinal peptid (VIP), NO donörleri ve tibolon. On yılı aşkındır gündemdeler, ancak FSD tedavisinde henüz kanıta dayalı bir başarı ve herhangi bir endikasyon için onaylanma rapor edilmedi.…”
Section: öStrojenunclassified